Mesenchymal Stem Cell-Derived Exosomes Hold Promise in the Treatment of Diabetic Foot Ulcers - Wang H; Wu S; Bai X; Pan D; Ning Y; Wang C; Guo L; Guo J; Gu Y (International Journal of Nanomedicine)
Hui Wang,1,* Sensen Wu,1,* Xinyu Bai,2 Dikang Pan,1 Yachan Ning,1 Cong Wang,1 Lianrui Guo,1 Jianming Guo,1 Yongquan Gu1 1Department of Vascular Surgery, Xuanwu Hospital, Capital Medical University, Beijing, 100053, People’s Republic of China; 2Department of Ophthalmology, The Second Hospital of Jilin University, Changchun, Jilin Province, 130033, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongquan Gu; Jianming Guo, Department of Vascular Surgery, Xuanwu Hospital, Capital Medical University, No. 45, Changchun Street, Beijing, 100053, People’s Republic of China, Tel +86 15311614369, Email gu15901598209@aliyun.com; jianmingguoxuanwu@163.comAbstract: Diabetic foot ulcers (DFU) represent one of the most common side effects of diabetes, significantly impacting patients’ quality of life and imposing considerable financial burdens on families and society at large. Despite advancements in therapies targeting lower limb revascularization and various medications and dressings, outcomes for patients with severe lesions remain limited. A recent breakthrough in DFU treatment stems from the development of mesenchymal stem cells (MSCs). MSCs have shown promising results in treating various diseases and skin wounds due to their ability for multidirectional differentiation and immunomodulation. Recent studies highlight that MSCs primarily repair tissue through their paracrine activities, with exosomes playing a crucial role as the main biologically active components. These exosomes transport proteins, mRNA, DNA, and other substances, facilitating DFU treatment through immunomodulation, antioxidant effects, angiogenesis promotion, endothelial cell migration and proliferation, and collagen remodeling. Mesenchymal stem cell-derived exosomes (MSC-Exo) not only deliver comparable therapeutic effects to MSCs but also mitigate adverse reactions like immune rejection associated with MSCs transplantation. This article provides an overview of DFU pathophysiology and explores the mechanisms and research progress of MSC-Exo in DFU therapy. Keywords: diabetic foot ulcer, DFU, mesenchymal stem cells, MSCs, exosomes, skin repair, regeneration, angiogenesis